2022
DOI: 10.18343/jipi.27.1.120
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan Kualitas Kimia Tanah Sulfat Masam dengan Aplikasi Kombinasi Bahan Organik Lokal dan Limbah Agroindustri

Abstract: The purpose of this research was to assess effect of compost treatment from various local organic materials combined with agro-industrial waste to improved chemical quality of acid sulfate mineral soils, to compare of root dry weight and grain weight milled dryness of Inpara-3. This research was conducted at screen house of Polytechnic Hasnur, Barito Kuala District, South Kalimantan from November 2020 to June 2021. This study used Compeletely Randomized Design (CRD) with Tukey's Honestly Significant Difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
0
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
2
0
0
2
Order By: Relevance
“…It is suspected that the provision of rice harvest wastes is able to create a conducive environment for growth and provide additional nutrients, especially Si, organic C, total Mg, and K in the formation of the number of panicles which can influence the number of grains. This is in line with research by Abdillah & Widiyastuti (2022) which showed that the use of rice straw compost and crumb rubber solid waste resulted in a higher weight of unhusked dry grain as compared to the control. If plant tissue in the soil is decomposed due to the activities of various organisms, various organic and inorganic compounds will be produced.…”
Section: Growth and Yield Of Rice Plantssupporting
confidence: 91%
See 1 more Smart Citation
“…It is suspected that the provision of rice harvest wastes is able to create a conducive environment for growth and provide additional nutrients, especially Si, organic C, total Mg, and K in the formation of the number of panicles which can influence the number of grains. This is in line with research by Abdillah & Widiyastuti (2022) which showed that the use of rice straw compost and crumb rubber solid waste resulted in a higher weight of unhusked dry grain as compared to the control. If plant tissue in the soil is decomposed due to the activities of various organisms, various organic and inorganic compounds will be produced.…”
Section: Growth and Yield Of Rice Plantssupporting
confidence: 91%
“…The p6 treatment showed that the average plant height was relatively higher than the other treatments, although statistically is not different. This is in line with research by Andayani & Hayat (2019) and Abdillah & Widiyastuti (2022). Research by Andayani & Hayat (2019) shows that the use of oil palm empty fruit bunches and rice husk charcoal can increase the height of rice plants in acid sulphate soil.…”
Section: Growth and Yield Of Rice Plantssupporting
confidence: 89%
“…Aksi nasional ketahanan pangan dan gizi bagi masyarakat telah menjadi program pemerintah yang wajib dilakukan oleh setiap pemerintah daerah (Mardya et al, 2023;Nurahadiyatika et al, 2022) Beberapa penelitian telah melaporkan rendahnya produksi padi yang dibudidayakan di tanah sulfat masam sehingga memerlukan pengelolaan air dan penerapan bahan organik yang tepat (Koesrini et al, 2020;Ratmini, 2018;Subiksa & Sukristyonubowo, 2021). Abdillah & Widiyastuti (2022) Mekanisme adsorbsi kimia dari biochar juga berperan dalam menekan kembalinya logam agar tidak berdampak pada penurunan pH tanah saat terjadi reduksi (Yang et al, 2021). Chang et al (2021) dan (Yulnafatmawita et al, 2023) Penerapan biochar mampu menurunkan degradasi hara makro dan mikro akibat kelarutan, perlindian, fiksasi dan dominasi logam (Alotaibi et al, 2021;Bilias et al, 2023;Neththasinghe et al, 2023;Rasuli et al, 2022;Wu et al, 2022;Xiu et al, 2023).…”
Section: Pendahuluanunclassified
“…Apabila ada harga yang terpatok tinggi serta akan menimbulkan kesulitan bagi petani atau pembudidaya. Perlunya penanganan yang tepat menjadikan hal penting dalam terjadinya jerapan Fosfat, karena factor diatas maka ketidaktahuan para pembudidaya dan petani menjadikan factor penentu suksesi budidaya [3]- [5] Dewasa ini, digitalisasi sudah mengubah cara konvensional menjadi sebuah sistem digital berupa teks, audio, angka, dan visual. Dalam hal ini, prosesi digitalisasi menjadi kebutuhan mutlak yang tidak bisa dihindari dan haruslah dihadapi.…”
Section: Pendahuluanunclassified